The Influence Of Age On Patient Attitudes And Acceptability Towards Using Their Own Mobile Device To Record Patient-Reported Outcomes Data In Clinical Trials - Byrom, B; Muehlhausen, W; Flood, E; Cassedy, C; Skerritt, B; McCarthy, M (Value in health, 2017)
OBJECTIVES: To evaluate the influence of age on attitudes towards the use of "bring your own device" (BYOD) to record patient-reported outcomes data in clinical trials. METHODS: Subjects entering a health questionnaire study using BYOD and a provisioned device were asked to complete a questionnaire assessing their attitudes towards BYOD use in clinical trials. RESULTS: 155 subjects (72 male, 83 female) aged 19-69 years [mean 48.6 ± 13.1; 19-40: 43 (28%), 41-60: 80 (52%), >60: 32 (21%)] with a range of conditions resulting in chronic pain entered the single-center study. Proportionately more >60 year olds presented with tablet devices compared to the other age groups (9%, 10% and 38%, respectively). 16 subjects (10%) encountered difficulties downloading the study app (2%, 14% and 13% of the three age categories, respectively). More subjects >60 years were unfamiliar downloading apps (0%, 2.5% and 12.5% respectively), and fewer felt definitely/probably able to download a study app without assistance (95%, 94% and 81% respectively). Over 90% of subjects in each age category would definitely or probably be willing to download an app on their own device for a forthcoming trial, with 135 (87%) reporting no concerns in doing so. Of those identifying a concern, a higher proportion were >60 years old (12%, 10% and 22%, respectively). A lower proportion of the youngest age group identified that a provisioned device would be more convenient (7%, 15% and 13%, respectively). CONCLUSIONS: Amongst our sample there was good acceptance for the use of BYOD in clinical trials including subjects >60 years old, though those over 60 were more likely to identify concerns about downloading the app. Concerns cited could be mitigated by assistance downloading, training, information and good app design. This study required subjects to use their own mobile device, and attitudes in the wider population may differ.